Structured silicalite‐1 encapsulated Ni catalyst supported on SiC foam for dry reforming of methane. Issue 4 (31st December 2020) - Chen, Huanhao; Shao, Yan; Mu, Yibing; Xiang, Huan; Zhang, Rongxin; Chang, Yabin; Hardacre, Christopher; Wattanakit, Chularat; Jiao, Yilai; Fan, Xiaolei
Abstract: Structured silicalite‐1 zeolite encapsulated Ni catalyst supported on silicon carbide foam (i.e., Ni@S1‐SiC) was prepared using a new yet simple one‐pot method, showing the significantly improved anti‐sintering and anti‐coking performance in comparison with the conventional supported and encapsulated Ni catalysts (i.e., Ni/S1, Ni/S1‐SiC, and Ni@S1), in catalytic dry reforming of methane (DRM). The developed Ni0.08 @S1‐SiC catalyst showed high CO2 /CH4 conversions of >85% and H2 /CO molar ratio of >0.85 at 700°C, outperforming other control catalysts under investigation. Additionally, the Ni0.08 @S1‐SiC catalyst demonstrated high turnover frequency (TOF) values of 5.6 and 2.1/s regarding to CO2 /CH4 conversions at 400°C, exhibiting excellent stability and low pressure‐drop during 100 hr on stream evaluation. Post‐reaction characterization of the used catalysts demonstrated that the combination of zeolite encapsulated Ni catalysts and SiC foam enabled well‐dispersed and ultrafine Ni nanoparticles, low pressure drop and intensified transfer steps, presented excellent anti‐sintering and anti‐coking abilities.